How Entrepreneurial Competencies Can Effect Business Performance - Nuryanti, B Lena; Hanifah, Ajeng Putri (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
The ability to build a business is one of the challenges as well as competencies that must be possessed by entrepreneurs today. This study explains what entrepreneurial competencies must be possessed by an entrepreneur to have good business performance. Because the ultimate goal of running a business is to achieve business success. This study aims to obtain 1) the effect of knowledge on business performance, 2) the effect of skills on business performance, 3) individual abilities on business performance in 2013 business education alumni by using a quantitative research approach. The results of the study found that the description of Entrepreneurial Competence for the 2013 Business Education alumni at UPI was in the fairly good category, the Business Performance Description for the 2013 Business Education alumni at UPI was in the medium category, and the magnitude of the influence of the Entrepreneurial Competency dimension on Business Success partially, namely, the Knowledge dimension. not complex, so it will affect Business Performance. Meanwhile, the Individual Ability dimension does not affect Business Performance. Meanwhile, simultaneously (overall) there is a positive and significant influence.